Beta-Amylase and Phosphatidic Acid Involved in Recalcitrant Seed Germination of Chinese Chestnut - Liu, Yang; Zhang, Yu; Zheng, Yi; Nie, Xinghua; Wang, Yafeng; Yu, Wenjie; Su, Shuchai; Cao, Qingqin; Qin, Ling; Xing, Yu (Frontiers in Plant Science, 2022)
Chinese chestnut (Castanea mollissima), a species with recalcitrant seeds, is an important source of nuts and forest ecosystem services. The germination rate of recalcitrant seeds is low in natural habitats and decreases under conditions of desiccation and low temperature. The germination rate of cultivated Chinese chestnut seeds is significantly higher than that of wild seeds. To explore the reasons for the higher germination rate of cultivated seeds in Chinese chestnut, 113,524 structural variants (SVs) between the wild and cultivated Chinese chestnut genomes were detected through genome comparison. Genotyping these SVs in 60 Chinese chestnut accessions identified allele frequency changes during Chinese chestnut domestication, and some SVs are overlapping genes for controlling seed germination. Transcriptome analysis revealed downregulation of the abscisic acid synthesis genes and upregulation of the beta-amylase synthesis genes in strongly selected genes of cultivated seeds. On the other hand, hormone and enzyme activity assays indicated a decrease in endogenous ABA level and an increase in beta-amylase activity in cultivated seeds. These results shed light on the higher germination rate of cultivated seeds. Moreover, phosphatidic acid synthesis genes are highly expressed in seed germination stages of wild Chinese chestnut and may play a role in recalcitrant seed germination. These findings provide new insight into the regulation of wild seed germination and promote natural regeneration and succession in forest ecosystems.